(3JGQjN GHf CHj GdgLGAs
(3ChdgG (B:s
(3GdMeO ddg QH GdYGdejf , hGdUdGI hGdSdGe Ydi SjOfG eMeO GdfHi hBdg hUMHg CLeYjf s
(3BNQgG (B:s
(3jfJgi Edi SfI (B589 (3ai YUQ GdSdWGf UdGM GdOjf jhSa Hf CjhH hMQhHg eY GdUdjHjjf s
(3GdeDda cGf eYGUQkG ddSdWGf UdGM GdOjf GdCjhHi GdeJhai SfI (B589(3g`s
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B6 - (3U (B7 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B8 - (3U (B255s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA JGQjN (B- (3bSe (B3 - (3U (B56 s
(3eUOQ GbJfGA GdCUd (B:s
(3GdCMeOjI HJhfS (B(4915) s
Keywords: (3GdJGQjNs